Topological superconductivity in full shell proximitized nanowires - Lutchyn, Roman; Winkler, Georg W.; van Heck, Bernard; Karzig, Torsten; Flensberg, Karsten; Glazman, Leonid I.; Nayak, Dr. Chetan (Bulletin of the American Physical Society, 2019)
We consider a new model system supporting Majorana zero modes based on semiconductor nanowires with a full superconducting shell. We demonstrate that, in the presence of spin-orbit coupling in the semiconductor induced by a radial electric field, the winding of the superconducting order parameter leads to a topological phase supporting Majorana zero modes. The topological phase persists over a large range of chemical potentials and can be induced by a predictable and weak magnetic field piercing the cylinder. The system can be readily realized in semiconductor nanowires covered by a full superconducting shell, opening a pathway for realizing topological quantum computing proposals.